Anode active material, anode material, alkaline ion battery including said anode material, and method for manufacturing anode active material

A heterostructured sulfide of transition metal elements M1 and M2, formed using a metal organic framework and heat treatment, addresses the need for improved cycle characteristics in alkaline ion batteries, enhancing their performance and durability.

JP7618135B2Active Publication Date: 2025-01-21JIKU CHEM CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021020949
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-12
Publication Date
2025-01-21
Estimated Expiration
2041-02-12

AI Technical Summary

Technical Problem

There is a strong demand for improving the cycle characteristics of negative electrode materials in alkaline ion batteries, particularly in sodium ion batteries, to enhance their performance and durability.

Method used

The development of a negative electrode active material comprising a sulfide of transition metal elements M1 and M2, where M1 and M2 are different metals, with a heterostructure, such as CoS2/NiS2, is achieved by a method involving the use of a metal organic framework (MOF) and heat treatment to form a stable, electron/ion transport-enhancing structure.

Benefits of technology

The resulting negative electrode material provides alkaline ion batteries with excellent cycle characteristics, demonstrated by high coulombic efficiency and specific capacity retention over multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618135000001
    Figure 0007618135000001
  • Figure 0007618135000002
    Figure 0007618135000002
  • Figure 0007618135000003
    Figure 0007618135000003
Patent Text Reader

Abstract

To provide a negative electrode active material that can bring excellent cycle characteristics to an alkaline ion battery, a negative electrode material, an alkaline ion battery including the negative electrode material, and a manufacturing method of the negative electrode active material.SOLUTION: A negative electrode active material for an alkaline ion battery according to the present invention includes a sulfide of a transition metal element M1 and a metal element M2, the transition metal element M1 and the metal element M2 are different metal elements, and the transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe, and V, and the metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag, and Cu.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode active material, a negative electrode material, an alkali ion battery including the negative electrode material, and a method for producing the negative electrode active material. [Background technology]

[0002] Metal sulfides have excellent redox reaction properties, thermal stability, and mechanical performance, making them promising compounds to be used as anode active materials in alkaline ion batteries, such as high-performance sodium ion batteries (SIBs).

[0003] For example, Non-Patent Document 1 proposes the use of CoS2 fixed to a sponge-like carbon matrix, synthesized by freeze-drying and hydrothermal processes, as the negative electrode material for sodium ion batteries. It is believed that such a negative electrode material can significantly improve the storage performance of sodium ion batteries. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Chemical Engineering Journal 332 (2018) 370-376 Summary of the Invention [Problem to be solved by the invention]

[0005] However, in recent years, in the field of batteries, there has been a strong demand for further improvement in cycle characteristics, and accordingly, there has been a demand for the development of battery materials capable of providing excellent cycle characteristics. From this perspective, it can be said that the development of a negative electrode active material that can provide excellent cycle characteristics when applied to the negative electrode material of an alkali ion battery is extremely important in the field of batteries.

[0006] The present invention has been made in consideration of the above, and aims to provide a negative electrode active material that can provide an alkali ion battery with excellent cycle characteristics, a negative electrode material, an alkali ion battery including the negative electrode material, and a method for manufacturing the negative electrode active material. [Means for solving the problem]

[0007] In order to achieve the above object, the present inventors have conducted extensive research and have investigated ways to enhance the structural stability of metal sulfides themselves and promote electron / ion transport by imparting a heterostructure to metal sulfides. As a result of such investigations, the present inventors have found that the above object can be achieved by using sulfides of specific transition metal elements as constituent components, and have thus completed the present invention.

[0008] That is, the present invention includes, for example, the subject matter described in the following sections. Item 1 In the negative electrode active material for an alkaline ion battery, Contains a sulfide of a transition metal element M1 and a metal element M2, The transition metal element M1 and the metal element M2 are different metal elements, The transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe, and V, The metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag and Cu. Section 2 Item 2. The negative electrode active material according to item 1, wherein the sulfide has a part of the transition metal element M1 replaced with the metal element M2. Section 3 Item 3. The negative electrode active material according to item 1 or 2, which is a particle having an octahedral structure. Section 4 Item 4. A negative electrode material comprising the negative electrode active material according to any one of items 1 to 3. Section 5 Item 5. An alkaline ion battery comprising the negative electrode material according to item 4. Section 6 A method for producing a negative electrode active material according to any one of items 1 to 3, A step A1 of mixing the metal-organic framework (MOF) having the transition metal element M1 with a source of the metal element M2 to obtain a precursor; A step A2 of obtaining a product by heat-treating a raw material including the precursor, a sulfur source, and a solvent; A step B of calcining the product obtained in the step A2; The method for producing a negative electrode active material comprises the steps of: Effect of the Invention

[0009] The negative electrode active material of the present invention can provide excellent cycle characteristics to an alkaline ion battery. [Brief description of the drawings]

[0010] [Figure 1] 1A shows an SEM image of the negative electrode active material obtained in Example 1, and FIG. 1B shows an SEM image of the negative electrode active material obtained in Comparative Example 1. [Diagram 2] In the SEM image of FIG. 1(a), elemental mapping images of sulfur (S), cobalt (Co), and nickel (Ni) are shown. [Diagram 3] 1 shows the results of X-ray diffraction measurement (XRD) of the negative electrode active materials obtained in Example 1 and Comparative Example 1. [Figure 4] FIG. 2 is a schematic diagram showing a part of the structure of the negative electrode active material obtained in Example 1. [Diagram 5] 1A shows the results of a constant current charge / discharge test using the battery assembled in Preparation Example 1, and FIG. 1B shows the results of a constant current charge / discharge test using the battery assembled in Preparation Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expressions "containing" and "comprise" include the concepts of "containing", "comprises", "consists essentially of" and "consists only of".

[0012] 1.Negative electrode active material The negative electrode active material for an alkali ion battery of the present invention contains a sulfide of a transition metal element M1 and a metal element M2. Here, the transition metal element M1 and the metal element M2 are different metal elements, the transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe, and V, and the metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag, and Cu. The negative electrode active material of the present invention can be used as a negative electrode material for constituting an alkali ion battery (e.g., a sodium ion battery), and can provide excellent cycle characteristics to the alkali ion battery.

[0013] The transition metal element M1 is preferably Co, since this tends to provide an alkaline ion battery with better cycle characteristics. Therefore, the sulfide of the transition metal element M1 is preferably a sulfide of Co (for example, CoS2).

[0014] The transition metal element M1 contained in the sulfide may be of only one type, or may contain two or more types.

[0015] As described above, the negative electrode active material of the present invention further contains a metal element M2 different from the transition metal element M1 in addition to the sulfide of the transition metal element M1. The metal element M2 contained in the negative electrode active material may be only one type, or may contain two or more types.

[0016] The metal element M2 is preferably Ni, since this tends to provide superior cycle characteristics to the alkaline ion battery.

[0017] In the negative electrode active material of the present invention, the state of existence of the metal element M2 is not particularly limited. For example, the metal element M2 can be present by replacing the transition metal element M1 in the sulfide. Specifically, the sulfide can have a structure in which a part of the transition metal element M1 is replaced by the metal element M2 (that is, in the negative electrode active material of the present invention, the transition metal element M2 can be present, for example, in the framework of the sulfide of the transition metal element M1). In this case, the negative electrode active material is likely to provide better cycle characteristics to an alkaline ion battery.

[0018] The presence of the metal element M2 in the framework of the sulfide of the transition metal element M1 can be determined, for example, by various known methods, and as an example, can be determined from the XRD spectrum of the negative electrode active material.

[0019] In the negative electrode active material, the ratio of the transition metal element M1 and the metal element M2 is not particularly limited. For example, the molar ratio of the transition metal element M1 and the metal element M2 in the negative electrode active material, M1:M2, is preferably 1:0.2 to 1:5, and more preferably 1:1 to 1:4. This allows the negative electrode active material to provide better cycle characteristics to an alkali ion battery.

[0020] In the negative electrode active material, the transition metal element M1, the metal element M2, and the sulfur atoms are preferably uniformly dispersed throughout the negative electrode active material. The dispersion state of the transition metal element M1, the metal element M2, and the sulfur atoms in the negative electrode active material can be grasped, for example, by element mapping based on a SEM image.

[0021] The negative electrode active material may contain other components to the extent that the effect of the present invention is not impaired, so long as it contains the sulfide of the transition metal element M1 and the metal element M2 as essential components. For example, the negative electrode active material may contain metals other than the transition metal element M1 and the metal element M2, and examples of such metal elements include metal elements that are inevitably contained in the negative electrode active material. In the negative electrode active material of the present invention, the total mass of the sulfide of the transition metal element M1 and the transition metal element M2 is preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 99% by mass or more. The negative electrode active material of the present invention may be composed of only the sulfide of the transition metal element M1 and the transition metal element M2.

[0022] The negative electrode active material is, for example, in the form of a solid such as a powder, but the shape is not particularly limited and can be formed in various shapes, and it is particularly preferable that the negative electrode active material is in the form of particles. When the negative electrode active material is in the form of particles, the shape can be, for example, in various shapes.

[0023] In particular, the negative electrode active material is preferably particles having an octahedral structure, since this can provide an alkaline ion battery with better cycle characteristics. Whether the negative electrode active material is particles having an octahedral structure can be determined from a scanning electron microscope (SEM) image of the negative electrode active material.

[0024] When the negative electrode active material is particulate, the average particle diameter is not particularly limited, and can be, for example, 50 to 1000 nm. In this case, the negative electrode active material is likely to bring about excellent cycle characteristics to an alkaline ion battery. The average particle diameter of the negative electrode active material is not particularly limited, and is preferably 80 to 800 nm, more preferably 100 to 600 nm, and even more preferably 120 to 500 nm. The average particle diameter here refers to the arithmetic average value of 50 particles randomly selected by direct observation of the negative electrode active material with a scanning electron microscope, and the circle equivalent diameters of these particles are measured.

[0025] The method for producing the negative electrode active material is not particularly limited. For example, the negative electrode active material of the present invention can be produced by a production method including steps A1, A2, and B described below.

[0026] 2. Method for producing negative electrode active material The method for producing a negative electrode active material of the present invention can include, for example, the following steps A1, A2, and B. Step A1: A step of mixing a metal-organic framework (MOF) having a transition metal element M1 with a source of a metal element M2 to obtain a precursor. Step A2: A step of obtaining a product by heat-treating a raw material containing the precursor, a sulfur source, and a solvent. Step B: A step of calcining the product obtained in step A2.

[0027] By the production method including the above steps A1, A2 and B, a negative electrode active material can be produced, for example, the above-mentioned negative electrode active material of the present invention can be produced.

[0028] (Process A1) Step A1 is a step for obtaining a precursor by mixing a metal-organic framework (MOF) having a transition metal element M1 with a source of a metal element M2. The transition metal element M1 and the metal element M2 are different metal elements.

[0029] The transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe and V, and is preferably Co. The metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag and Cu, and is preferably Ni. In the metal organic framework having the transition metal element M1, the transition metal element M1 may be only one type, or may contain two or more types. The metal element M2 may be only one type, or may contain two or more types.

[0030] Examples of the metal organic framework having a transition metal element M1 (hereinafter simply referred to as a "metal organic framework") include various metal organic frameworks (MOFs).

[0031] As long as the metal organic framework contains the transition metal element M1, for example, a wide variety of known metal organic frameworks can be mentioned. Specific examples of such metal organic frameworks, when the transition metal element M1 is Co, include ZIF-67 (2-Methylimidazole cobalt salt), Co(MeIM)2 (MEIM means 2-methylimidazole. The same applies below), Co-THT (THT means triphenylene hexathiol. The same applies below), and Co3(THT)2H3. When the transition metal element M1 is Zn, ZIF-8 and Zn(MeIM)2 can be mentioned. When the transition metal element M1 is Ni, Ni-BHT (BHT means benzene hexathiol. The same applies below), Ni3(BTC)2 (BTC means benzene tricarboxylate. The same applies below), and Ni-THT (triphenylene hexathiol) can be mentioned. When the transition metal element M1 is Fe, examples of the transition metal element include Fe-MIL-88A (MIL stands for Metalial sofistitute Lavoisier frameworks, hereinafter the same), Fe3O(FA)3-(H2O)2(NO3) (FA stands for fumaric acid), MIL-100, and Benzene-1,3,5-tricarboxylate; iron (3+); hydrate. When the transition metal element M1 is Cu, examples of the transition metal element include Cu-BHT, Cu3(BHT)2, and CuBDC (BDC stands for 1,4-benzenedicarboxylate, hereinafter the same). When the transition metal element M1 is Mn, examples of the transition metal element include Mn-BTC. When the transition metal element M1 is Mo, examples of the transition metal element include Mo-BTC.

[0032] The metal-organic framework is preferably a metal-organic framework containing Co, and among these, ZIF-67 is particularly preferred, in that the resulting negative electrode active material is likely to provide excellent cycle characteristics to an alkali ion battery.

[0033] The metal organic framework having the transition metal element M1 can be produced, for example, by a known method, or can be obtained from a commercial product.

[0034] The source of the metal element M2 (hereinafter simply referred to as "M2 source") may be the metal element M2 alone or a compound containing the metal element M2, but is preferably a compound containing the metal element M2.

[0035] The type of compound containing the metal element M2 is not particularly limited, and examples thereof include various inorganic compounds containing the metal element M2. Examples of inorganic compounds containing the metal element M2 include oxides of the metal element M2, compounds containing oxoanions of the metal element M2 (metal acid salts), as well as nitrates, sulfates, chlorides, chlorates, perchlorates, chloride complexes, carbonates, hydrogencarbonates, phosphates, and hydrogenphosphates of the metal element M2. Among these, inorganic compounds containing the metal element M2 are preferably nitrates, compounds containing oxoanions, and chloride complexes of the metal element M2. Examples of inorganic compounds containing the metal element M2 include Ni(NO3)2, Na2MoO4, HAuCl4, H2PtCl6, AgNO3, and Cu(NO3)2.

[0036] The M2 source may include various organic compounds of the transition metal element M2, such as acetates, oxalates, formates, and succinates of the transition metal element M1.

[0037] In step A1, the metal organic framework (MOF) having the transition metal element M1 and the source of the metal element M2 can be mixed in a solvent. Examples of such a solvent include water, alcohol-based solvents such as ethanol and isopropanol, and ketone-based solvents such as acetone and methyl ethyl ketone. The metal organic framework and the source of M2 can also be mixed after being dispersed or dissolved in a solvent in advance.

[0038] The mixing conditions in step A1 are not particularly limited, and mixing can be carried out, for example, at 10 to 50° C. (preferably 20 to 35° C.), and the mixing time can be appropriately selected depending on the temperature.

[0039] In step A1, the metal organic framework and the M2 source are mixed to obtain a precursor as a solid content. Such solid content can be separated and washed by an appropriate method. The precursor obtained in step A1 may have a structure in which a part of the transition metal element M1 in the metal organic framework having the transition metal element M1 is replaced by the metal element M2.

[0040] In step A1, the ratio of the metal organic framework and the M2 source used is not particularly limited. For example, it is preferable to use the metal organic framework and the M2 source so that the molar ratio of the transition metal element M1 and the metal element M2 contained in the metal organic framework, M1:M2, is 1:0.2 to 1:5, preferably 1:1 to 1:4. This allows the resulting negative electrode active material to provide better cycle characteristics to an alkali ion battery.

[0041] (Process A2) Step A2 is a step for obtaining a product by heat-treating a raw material containing the precursor obtained in step A1, a sulfur source, and a solvent.

[0042] The sulfur source used in step A2 may be elemental sulfur or a compound containing sulfur, but is preferably a compound containing sulfur.

[0043] Examples of the sulfur-containing compound include a wide variety of known sulfur compounds, such as thioacetamide (CHCSNH), thiourea (SC(NH)), cysteine ​​(CHNOS), sodium thiosulfate (NaS0), ammonium sulfide ((NH)S), sodium sulfide (NaS), etc. In addition, in the sulfur-containing compound, a part of the sulfur element may be replaced with Se and / or Te element.

[0044] The sulfur source can be used alone or in combination of two or more kinds.

[0045] The raw materials used in step A2 include a precursor, a sulfur source, and a solvent. As the solvent, water can be used, and various organic solvents can also be used. Examples of the organic solvent include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), oleic acid, oleamide, ethylene glycol, octadecene, and ethylenediamine. The solvent used in step A2 can also be a mixture of water and an organic solvent.

[0046] The solvent used in step A2 may contain various additives. Examples of additives include ammonia water, polyvinylpyrrolidone (PVP), cetyltrimethylammonium bromide (CTAB), sodium lauryl sulfonate (SDS), ethylenediaminetetraacetic acid (EDTA), and other dispersion stabilizers and surfactants. When the solvent contains an additive, it becomes easier to obtain a negative electrode active material having the layer-by-layer structure described above. When the solvent contains an additive, the content of the additive relative to the total mass of the solvent may be 5% by mass or less, preferably 3% by mass or less, and more preferably 1% by mass or less.

[0047] In the raw materials used in step A2, the content ratio of the precursor, the sulfur source, and the solvent is not particularly limited. For example, in the raw materials used in step A2, the content ratio of the sulfur source is preferably 10 to 500 parts by mass, more preferably 30 to 300 parts by mass, and further preferably 50 to 250 parts by mass per 100 parts by mass of the total mass of the precursor, in that a sulfide of the transition metal element M1 is easily formed and a desired negative electrode active material is easily obtained.

[0048] The amount of the solvent contained in the raw material used in step A2 is not particularly limited. For example, the amount of the solvent used in the raw material can be adjusted so that the concentration of the transition metal element M1 in the raw material is 1 to 1000 mM, more preferably 10 to 500 mM, and even more preferably 20 to 100 mM.

[0049] In step A2, the raw material is heat-treated. This produces a product containing sulfide. For example, the heat treatment method includes a method in which the raw material is placed in a container, the container is sealed, and the container is heated. When the solvent in the raw material is water, this is called a hydrothermal synthesis method.

[0050] The temperature in the container during the heat treatment in step A2 is not particularly limited, and can be, for example, 80 to 400° C., and preferably 150 to 250° C. The heating time is also not particularly limited, and can be appropriately determined depending on the heating temperature, and can be, for example, 6 to 40 hours. The pressure in the container during the heat treatment can also be appropriately set.

[0051] In step A2, after the heat treatment is completed, the product can be extracted by an appropriate method. For example, when the product is obtained as a solid, the solid can be separated by a method such as centrifugation, washed and dried to obtain the product as a solid. The product obtained in step A2 is, for example, a sulfide having a structure in which part of the transition metal element M1 in the sulfide of the transition metal element M1 is replaced by a metal element M2.

[0052] (Process B) In step B, the product obtained in step A2 is calcined to obtain the desired negative electrode active material.

[0053] In step B, the firing method is not particularly limited, and a wide variety of known firing methods can be used. For example, the firing temperature can be 200 to 1000°C, preferably 220 to 800°C, more preferably 250 to 600°C, and even more preferably 280 to 500°C.

[0054] The calcination time may be appropriately selected depending on the calcination temperature, and may be, for example, 0.5 to 5 hours. In step B, the rate of temperature rise during calcination is not particularly limited and may be appropriately set, for example, 1 to 10° C. / min.

[0055] The calcination treatment may be carried out in air or in an inert gas atmosphere, and may be carried out using a known heating device such as a commercially available heating furnace.

[0056] By the calcination treatment in step B, for example, remaining by-products and unreacted raw materials such as a sulfur source can be removed, and the target negative electrode active material can be obtained with high purity, and the crystallinity of the obtained negative electrode active material can be increased.

[0057] According to the manufacturing method including the above-mentioned steps A and B, the negative electrode active material of the present invention can be easily obtained by a simple process, and the manufacturing method requires low energy. In addition, the raw materials used in the manufacturing process are inexpensive and can be obtained from abundant resources.

[0058] 3. Negative electrode materials The negative electrode material of the present invention may contain other components as long as it contains the above-mentioned negative electrode active material, and examples of such components include known components used in negative electrode materials for alkaline ion batteries (e.g., sodium ion batteries). For example, the negative electrode material of the present invention may contain a conductive assistant and a binder in addition to the above-mentioned negative electrode active material.

[0059] The conductive assistant may be, for example, a wide variety of known conductive assistants used to form electrode materials for various batteries. Examples of the conductive assistant include various carbon materials, such as hard carbon, soft carbon, graphene, reduced graphene oxide, natural graphite, artificial graphite, conductive carbon black, and carbon fibers. Examples of carbon fibers include carbon nanofibers and carbon nanotubes. Other conductive assistants include metal powders such as copper and nickel, metal fibers, and conductive ceramic materials.

[0060] Binder: For example, a wide range of known binders used to form electrode materials for various batteries can be used. Examples of binders include various resin materials, specifically, polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), polyethylene terephthalate, polyacrylonitrile (PAN), polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyethylene, polypropylene, etc.

[0061] The content of the negative electrode active material in the negative electrode material is not particularly limited. For example, the content of the negative electrode active material is preferably 50 to 95 mass %, more preferably 60 to 90 mass %, based on the total mass of the negative electrode active material, conductive assistant, and binder contained in the negative electrode material.

[0062] The content of the conductive assistant in the negative electrode material is not particularly limited. For example, the conductive assistant is preferably contained in an amount of 3 to 30 mass %, more preferably 5 to 20 mass %, based on the total mass of the negative electrode active material, the conductive assistant, and the binder contained in the negative electrode material.

[0063] The content of the binder in the negative electrode material is not particularly limited. For example, the binder is preferably contained in an amount of 3 to 30 mass %, more preferably 5 to 20 mass %, based on the total mass of the negative electrode active material, conductive assistant, and binder contained in the negative electrode material.

[0064] The negative electrode material may be composed of only a negative electrode active material, a conductive assistant, and a binder, or may contain other components.

[0065] The method for preparing the negative electrode material is not particularly limited, and for example, a known method for preparing a negative electrode material can be widely adopted. For example, the negative electrode material can be prepared by mixing the negative electrode active material, the conductive assistant, and the binder in a predetermined ratio by an appropriate method. When preparing the negative electrode material, a solvent can be used to disperse the negative electrode active material, the conductive assistant, and the binder. Examples of the solvent include water and various organic solvents, such as lower alcohol compounds having 1 to 3 carbon atoms, NMP (N-methyl-2-pyrrolidone), etc. When the positive electrode material contains a solvent, it is, for example, in the form of a slurry or a paste.

[0066] 4. Alkaline ion battery The alkali ion battery of the present invention is not particularly limited in other configurations as long as it includes the negative electrode material, and may have, for example, the same configuration as a known alkali ion battery. The type of the alkali ion battery is not particularly limited, and examples thereof include a sodium ion secondary battery, a lithium ion secondary battery, and a potassium ion secondary battery.

[0067] The alkaline ion battery may include, for example, a positive electrode, a negative electrode, an electrolyte, and a separator. The size and shape of the battery may be appropriately determined depending on the application.

[0068] The positive electrode can have a structure composed of, for example, a metal foil and a positive electrode material. Examples of metals for forming the metal foil include aluminum, titanium, platinum, molybdenum, stainless steel, and copper. Known positive electrode materials can be widely used as the positive electrode material. For example, materials constituting the positive electrode material include sodium metal, lithium metal, NaFePO4, Na3V2(PO4)3, Na x MO4(M=Co, Mn, V, Fe), LiTiS2, LiCoO2, LiNiO2, LiMnO2, LiNi 0.33 Mn 0.33 Co0.33 O2, LiNi 0.8 Mn 0.15 Al 0.05 O2, LiMn2O4, LiFePO4, etc. The positive electrode can be prepared by a known method, for example, a method of coating a positive electrode material on a metal foil.

[0069] The negative electrode may have a structure in which the negative electrode active material of the present invention is supported on a metal foil. Examples of the metal foil include aluminum, titanium, platinum, molybdenum, stainless steel, copper, etc. The negative electrode may be produced by a known method.

[0070] In the alkaline ion battery, the type of electrolyte is not particularly limited, and for example, a known electrolyte used in a secondary battery can be used. The electrolyte may be either a solid electrolyte or a liquid electrolyte.

[0071] The liquid electrolyte may be a solution in which the electrolyte is dissolved in a solvent. The electrolyte may be various alkaline salts depending on the type of battery, such as NaPF6, NaClO4, NaCF3SO3, NaFSI, NaTFSI, LiPF6, LiClO4, LiBF4, LiBOB, LiAsF6, LiCF3SO3, LiTFSI, LiFSI, KPF6, KFSI, KTFSI, KBF4, and other known magnesium salts, aluminum salts, zinc salts, and other known salts. The solvent may be water, diglyme, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, propyl acetate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and the like.

[0072] Examples of solid electrolytes include inorganic materials such as sulfides and oxides, and polymeric materials such as PEO (polyethylene oxide).

[0073] As the separator, a known separator applied to a secondary battery can be used, and examples thereof include materials formed of polyolefin resins such as polyethylene and polypropylene; polyimide; polyvinyl alcohol; fluororesins such as aminated polyethylene oxide polytetrafluoroethylene; acrylic resins; nylon; aromatic aramid; inorganic glass; ceramics, etc. The separator can be in the form of a porous membrane, nonwoven fabric, woven fabric, etc. Other examples of the separator include various polymer membranes and inorganic electrolytes. Examples of inorganic electrolytes include LiLaTiO3, Li7La3Zr2O 12 (LLZO), Na3Zr2Si2PO 12 , Na 11 Sn2PS 12 , Na3PSe4, etc. EXAMPLES

[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the embodiments of these examples.

[0075] (Preparation Example 1: Preparation of a metal-organic framework having a transition metal element M1) With reference to the known literature (H. Liu, Z. Chen, L.Zhou, X. Li, K. Pei, J. Zhang, Y. Song, F. Fang, R. Che and D. Sun, J. Mater. Chem. A, 2019, DOI:10.1039 / C8TA12403E), ZIF-67 nanocubes were prepared by coprecipitation. First, 11.2 g of 2-methylimidazole was dissolved in 175 ml of distilled water while stirring to prepare a homogeneous solution (Co-containing solution). Meanwhile, 597 mg of Co(NO3)2·6H2O, 20 mg of hexadecyltrimethylammonium bromide, and 20 ml of distilled water were mixed and sonicated for 10 minutes to prepare a solution (2-MIM solution). Next, the transparent Co-containing solution was quickly added to the homogeneous 2-MIM solution to prepare a mixed solution, and the mixed solution was vigorously stirred at room temperature for 3 hours. This resulted in a purple precipitate of ZIF-67, which was finally separated by centrifugation, washed several times successively with distilled water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours to obtain ZIF-67 (a Co-containing metal-organic framework).

[0076] Example 1 80 mg of ZIF-67 obtained in Preparation Example 1 was weighed out, dispersed in 40 mL of ethanol, and ultrasonically treated for 30 minutes to prepare solution 1. Meanwhile, 200 mg of Ni(NO3)2 (hexahydrate) (M2 source) was dissolved in 10 mL of ethanol and ultrasonically treated for 10 minutes to prepare solution 2. The above-mentioned solutions 1 and 2 were mixed and stirred at room temperature (25 ° C) for 12 hours to obtain a solid content. The solid content was collected by centrifugation, washed three times each with distilled water and ethanol, and then vacuum dried at 60 ° C overnight to obtain a precursor of the negative electrode active material (step A1).

[0077] 100 mg of the precursor obtained as described above was dispersed in a mixed solution of 30 mL of deionized water and 1 mL of ammonia water (28% by mass concentration), to which 100 mg of thioacetamide (sulfur source) was added, and the mixture was stirred at room temperature (25°C) for 1 hour to obtain a suspension. The suspension was transferred to a 50 mL sealed autoclave lined with Teflon (registered trademark), the autoclave was sealed, and the mixture was heated at 200°C for 20 hours (step A2). The product in the autoclave was then collected by centrifugation, washed several times with distilled water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Finally, the product was calcined at 300°C for 1 hour under an argon atmosphere to obtain the desired negative electrode active material (step B). The obtained negative electrode active material was designated as "CoS2 / NiS2".

[0078] Comparative Example 1 100 mg of ZIF-67 was dispersed in a mixed solution of 30 mL of deionized water and 1 mL of ammonia water (28% by mass), to which 100 mg of thioacetamide was added, and the mixture was stirred at room temperature (25°C) for 1 hour to obtain a suspension. The suspension was transferred to a 50 mL Teflon-lined sealed autoclave, which was then sealed and heated at 200°C for 20 hours. The product in the autoclave was then collected by centrifugation, washed several times with distilled water and ethanol, and then dried in a vacuum oven at 60°C for 12 hours. Finally, the product was calcined at 300°C for 1 hour under an argon atmosphere to obtain CoS2.

[0079] (Example 1) A negative electrode material was prepared, which consisted of the "CoS2 / NiS2" obtained in Example 1 as the negative electrode active material, superP (conductive carbon black) as the conductive additive, and polyvinylidene fluoride (PVDF) as the binder. In this negative electrode material, CoS2 / NiS2:superP:PVDF=7.5:1.5:1 (mass ratio). N-methyl-2-pyrrolidone (NMP) was added as a solvent to this negative electrode material, and the mixture was stirred for 12 hours to mix uniformly. The obtained slurry was coated on copper foil, and dried in a vacuum at 120°C for 12 hours to produce a negative electrode. A battery was assembled by a known method using this negative electrode, a positive electrode (sodium metal with aluminum foil), a liquid electrolyte, and a separator ("Whatman GF / C glass fiber filter paper" provided by Cytiva) impregnated with the liquid electrolyte. The electrolyte was a 1M sodium trifluoromethanesulfonate solution, and the solvent for this solution was diglyme.

[0080] (Example 2) A battery was assembled in the same manner as in Preparation Example 1, except that the negative electrode active material was changed to CoS2 obtained in Comparative Example 1 instead of CoS2 / NiS2.

[0081] (Evaluation Results) 1(a) shows an SEM image of the negative electrode active material obtained in Example 1, and (b) shows an SEM image of the negative electrode active material obtained in Comparative Example 1. It was found that particles having an octahedral structure were formed in both negative electrode active materials, but the particles of the negative electrode active material obtained in Example 1 were found to have a larger size than the particles of the negative electrode active material obtained in Comparative Example 1.

[0082] Fig. 2(A) shows an image obtained by elemental mapping of sulfur element (S), cobalt element (Co), and nickel element (Ni) in the SEM image of Fig. 1(a). Fig. 2(B) shows an image obtained by mapping the framed area of ​​Fig. 2(A) with S, Co, and Ni. From the mapping results of Fig. 2, it was confirmed that S, Co, and Ni are uniformly distributed throughout the negative electrode active material in CoS2 / NiS2 obtained in Example 1.

[0083] 3 shows the results of X-ray diffraction measurement (XRD) of the negative electrode active materials obtained in Example 1 and Comparative Example 1. For the X-ray diffraction measurement, Rigaku's "SmartLab" was used, and the measurement was performed using a Cu-Kα (λ=1.540 Å) radiation source in the range of 2θ=10 to 100°.

[0084] In the XRD spectrum of Figure 3, the diffraction peaks of CoS2 / NiS2 are in good agreement with those of CoS2 (JCPDS card No. 41-1471) and NiS2 (JCPDS card No. 11-0099), and it was confirmed that no other diffraction peaks were observed. Note that the diffraction peaks of COS2 obtained in Comparative Example 1 are pure COS2 and correspond to the diffraction peaks of COS2 (JCPDS card No. 41-1471).

[0085] This XRD spectrum suggests that the CoS2 / NiS2 obtained in Example 1 is a metal sulfide CoS2 / NiS2 having a heterostructure, and is presumed to form a structure (framework) as shown in Fig. 4. In other words, it is understood that CoS2 / NiS2 has a structure in which the Ni element (Ni) is inserted into the framework of cobalt disulfide (CoS2) (a structure in which part of the Co in the sulfide is replaced by Ni).

[0086] FIG. 5(A) shows the results of a constant current charge / discharge test using the battery assembled in Preparation Example 1, and FIG. 5(B) shows the results of a constant current charge / discharge test using the battery assembled in Preparation Example 2. These measurements were performed using a LAND battery test system "CT2001A" (Wuhan LAND electronics Co., Ltd. China). The measurement temperature was 30°C, and the applied voltage was 1.5 to 3.5 V (5Ag -1 ) was decided.

[0087] As shown in FIG. 5A, in the battery of Preparation Example 1 having the CoS2 / NiS2 obtained in Example 1 as the negative electrode active material, after 400 cycles, 5Ag -1At a high current density of 492.6mAhg, the coulombic efficiency is about 100%. -1 In contrast, as shown in FIG. 5B, the battery of Preparation Example 2, which includes CoS2 of Comparative Example 1 as the negative electrode active material, can provide a specific capacity of 5Ag after 400 cycles. -1 At a high current density of 100%, the coulombic efficiency was about 100%, but the specific capacity was 240.1 mAhg -1 It remained at .

[0088] From the above, it was found that the alkali ion battery (sodium ion battery) having the CoS2 / NiS2 obtained in Example 1 as the negative electrode active material has excellent cycle characteristics. From the results of Example 1, it is theoretically presumed that the negative electrode active material of the present invention can provide an alkali ion battery with excellent cycle characteristics as long as the transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe, and V, and the metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag, and Cu.

Claims

1. In the negative electrode active material for an alkaline ion battery, Contains a sulfide of a transition metal element M1 and a metal element M2, The transition metal element M1 is Co; The negative electrode active material, wherein the metal element M2 is Ni.

2. The negative electrode active material according to claim 1 , wherein the sulfide has a part of the transition metal element M1 substituted with the metal element M2.

3. A negative electrode active material for an alkaline ion battery, comprising: Contains a sulfide of a transition metal element M1 and a metal element M2, The transition metal element M1 and the metal element M2 are different metal elements, The transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe, and V, The metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag, and Cu, The negative electrode active material is a particle having an octahedral structure.

4. A negative electrode material comprising the negative electrode active material according to any one of claims 1 to 3.

5. An alkali ion battery comprising the negative electrode material according to claim 4.

6. A method for producing a negative electrode active material for an alkali ion battery, comprising: The negative electrode active material is Contains a sulfide of a transition metal element M1 and a metal element M2, The transition metal element M1 and the metal element M2 are different metal elements, The transition metal element M1 is at least one selected from the group consisting of Co, Ni, Zn, Mo, Mn, Cu, Fe, and V, The metal element M2 is at least one selected from the group consisting of Ni, Mo, Au, Pt, Ag, and Cu, A step A1 of mixing the metal organic framework (MOF) having the transition metal element M1 with a source of the metal element M2 to obtain a precursor; A step A2 of obtaining a product by heat-treating a raw material including the precursor, a sulfur source, and a solvent; A step B of calcining the product obtained in the step A2; The method for producing a negative electrode active material comprises the steps of:

Citation Information

Patent Citations

  • Nonaqueous secondary battery

    JP1999162467A

  • Negative electrode active material and nonaqueous electrolyte battery

    JP2003086177A